Caracterización y análisis de los sistemas de medición que se usan en actividad forestal para la comercialización de maderas en troza y aserrada en la región Loreto – 2022 - Garcia Huaymana, Melissa Solangel (2024)
The present study was carried out in Loreto Region, with the purpose of characterizing and analyzing these measurement systems that are used in forestry activity for the commercialization of wood in its different ways. From the obtained results, it is clear that the metric and decimal systems that have been used to date imply serious losses for the logger. The persistence in the unofficial use of the Doyle rule has been generating serious economic losses for timber extractives. The production of log wood has experienced a very worrying drop that reaches 80.5% if we compare it with the production of 2016, this being one of the most flourishing years of logging activity. The timber forest resource is very varied. To date, more than 100 species are marketed, 57 of them are those with the highest production volume. Measuring tree heights presents the greatest difficulties, requires further studies to improve it. The export of wood in Loreto has disappeared due to the lack of raw materials and the lack of a shipping business to handle international transportation.